2017
DOI: 10.1103/physrevb.95.014112
|View full text |Cite
|
Sign up to set email alerts
|

Effective Hamiltonians, prethermalization, and slow energy absorption in periodically driven many-body systems

Abstract: We establish some general dynamical properties of quantum many-body systems that are subject to a high-frequency periodic driving. We prove that such systems have a quasi-conserved extensive quantity H * , which plays the role of an effective static Hamiltonian. The dynamics of the system (e.g., evolution of any local observable) is well-approximated by the evolution with the Hamiltonian H * up to time τ * , which is exponentially large in the driving frequency. We further show that the energy absorption rate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
341
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 320 publications
(356 citation statements)
references
References 35 publications
15
341
0
Order By: Relevance
“…A perturbative study of this 3D related model without disorder leads to a critical time crystal 23 . For general periodically driven systems, when subject to a high-frequency periodic driving, the energy absorption rate is exponentially small in the driving frequency for any initial state 24,25 , and it is shown that Floquet time crystals can be stabilized in the so-called prethermal phases without the need for strong disorder, before eventually heating into a thermal phase 26,27 . Another possibility is that the observed DTC falls into the short time regime before reaching the prethermal state, as suggested in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A perturbative study of this 3D related model without disorder leads to a critical time crystal 23 . For general periodically driven systems, when subject to a high-frequency periodic driving, the energy absorption rate is exponentially small in the driving frequency for any initial state 24,25 , and it is shown that Floquet time crystals can be stabilized in the so-called prethermal phases without the need for strong disorder, before eventually heating into a thermal phase 26,27 . Another possibility is that the observed DTC falls into the short time regime before reaching the prethermal state, as suggested in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The validity of the high-frequency approximation, neglecting resonant excitations within the lowenergy Hubbard description, has been studied for various scenarios in references [24,25,27,28,[30][31][32][33][34][35]. For systems with local energy bound, which includes the fermionic Hubbard model, it has been shown that the heating rates decrease exponentially with the driving frequency [36][37][38][39]. In this paper, we will address the validity of the lowfrequency approximation, where the resonant coupling to excited orbital states is neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Note that unlike Refs. [23][24][25][26], where the heating rate is proven to be O(exp( A )), we only obtain O(exp( A √ )). This can be traced back to the estimation of the convergence radius in Appendices B and C to be ρ n ∼ 1/n 2 , hence the squared residual norm μ n ∼ O(n 4n 2n ).…”
Section: B Quasiconserved Quantity By Sw Transformationmentioning
confidence: 99%
“…In particular, various works showed that systems with weak integrability breaking exhibit this phenomenon [20][21][22]. In addition, prethermalization has been shown rigorously to exist in periodically driven many-body systems under strong driving frequencies using the FloquetMagnus expansion [23,24] and renormalization technique [25,26]. The latter also applies to time-independent many-body systems, and in particular can be used to prove rigorously the presence of exponentially long relaxation times of "particles" such as doublons in the Hubbard model in the strong coupling limit [27][28][29].…”
Section: Introductionmentioning
confidence: 99%